LOGISTIC SYSTEM OF KAZAKHSTAN FROM THE POSITION OF INNOVATIVE PARADIGM (Journal of Economic Research & Business Administration, 2017)
The relevance of the topic under consideration is devoted to a deeper understanding of the fact that widespread digitalization poses ambitious tasks to modernize the economy of Kazakhstan. As you know, the digital economy will lead to the disappearance of whole industries and the emergence of new ones (one of which is logistics). Logistics, as a science, by virtue of its interdisciplinarity and as a branch of the economy should meet the global challenges of our time. Therefore, it is time to carry out a comparative analysis of the existing evolution and paradigms of the development of logistics as a science and its theoretical and applied continuation in the strategic plan – supply chain management.The purpose of this article is to show how a conceptual – categorical analysis of the historical aspects of the development of logistics and supply chain management on a global scale provides an understanding for the further development of the logistics system in Kazakhstan within the framework of innovative logistics – smart logistics and network technology for supply chain management. The scientific significance of this article is that if the scientific world has so far shared logistics and supply chain management as two scientific disciplines, then the author made an attempt using the category of «innovative paradigm» to show continuity of conceptual schemes of logistics and supply chain management and to produce a new Classification of types of logistics in accordance with modern challenges of society, such as: basic logistics-integrated logistics-innovative logistics-smart logistics-supply net. Thanks to the conducted research, the article determines the level of theory and practice of development of Kazakhstan’s logistics system in terms of business performance.Key words: logistics, paradigm, basic logistics, integrated logistics, innovative logistics.